A retrospective analysis of recurrent pediatric ependymoma reveals extremely poor survival and ineffectiveness of current treatments across central nervous system locations and molecular subgroups. Issue 9 (2nd July 2020) - Ritzmann, Timothy A.; Rogers, Hazel A.; Paine, Simon M.L.; Storer, Lisa C.D.; Jacques, Thomas S.; Chapman, Rebecca J.; Ellison, David; Donson, Andrew M.; Foreman, Nicholas K.; Grundy, Richard G.
Abstract: Background: Relapse occurs in 50% of pediatric ependymoma cases and has poor prognosis. Few studies have investigated the clinical progress of relapsed disease, and treatment lacks a standardized approach. Methods and materials: We analyzed 302 pediatric ependymoma cases. Tumor, demographic, and treatment variables were investigated for association with relapse risk, time to recurrence, and survival after relapse. DNA methylation profiling was performed for 135/302 cases, and predominant subgroups were EPN_PFA ( n  = 95) and EPN_RELA ( n  = 24). Chromosome 1q status was ascertained for 185/302 cases by fluorescent in‐situ hybridization (FISH), multiplex ligation‐dependent probe amplification (MLPA), and DNA methylation profiles. Results: Sixty‐two percent of cases relapsed, with a median of two recurrences with no difference between posterior fossa and supratentorial locations (66% vs 55% relapse rate). One hundred seventeen (38%) cases relapsed within two years and five (2%) beyond 10 years. The late relapses were clinically heterogeneous. Tumor grade and treatment affected risk and time to relapse variably across subgroups. After relapse, surgery and irradiation delayed disease progression with a minimal impact on survival across the entire cohort. In the EPN_PFA and EPN_RELA groups, 1q gain was independently associated with relapse risk (subhazard ratio [SHR] 4.307, P  = 0.027 and SHR 1.982, P  = 0.010, respectively) while EPN_PFA had increased relapse risk compared with EPN_RELA (SHR = 0.394, P  = 0.018). Conclusions: Recurrent pediatric ependymoma is an aggressive disease with poor outcomes, for which current treatments are inadequate. We report that chromosome 1q gain increases relapse risk in common molecular subgroups in children but a deeper understanding of the underlying biology at relapse and novel therapeutic approaches are urgently needed.